Peningkatan Kompetensi dan Kinerja Aparatur Sipil Negara (ASN) Melalui Pembelajaran Berbasis Digitalisasi Teknologi pada Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kabupaten Tapin - Hernilawati; Zakky Zamrudi; Syahrial Shaddiq (Jurnal Riset Multidisiplin Edukasi, 2025)
Civil Servants are government employees tasked with carrying out government functions in both the development sector and services to the community. The State Civil Apparatus (ASN) acts as planners, implementers, supervisors, public servants, and Agents of Change who are required to be professional, competent, efficient, and oriented towards the quality of public services. In this increasingly sophisticated technological era, they need to adapt to the changes in technological development, be capable of innovating creatively and adaptively, by utilizing digital technology to improve their competence and the quality of their service performance. However, in reality, there are still many ASNs who have not been able to optimize their competence and performance because they are still fixated on offline or face-to-face learning methods. The face-to-face learning method having several advantages, but it also has disadvantages including time constraints and a lack of flexibility, which makes it difficult for ASNs to balance their main duties and functions with the obligation to attend training; it requires other accommodation costs; there is an uneven availability of competent teachers or speakers in one area; there is limited capacity to accommodate all ASN competency development needs simultaneously; and many more. To overcome this problem, ASNs are required to be able to adapt to the existence of digitalization technology that provides an online learning system easily and with flexible timing. The government strives to provide convenience for ASNs who want to improve their competence by providing an artificial intelligence-based learning platform that can be accessed by ASNs anywhere and anytime without disrupting their main work. Therefore, the author wants to evaluate the extent to which the learning platform provided by the government can be used by ASNs to broaden their knowledge and improve their self-competence.